Diversidade social e violência: o professor como mediador de conflitos no ambiente escolar - Corrêa, Elizandro Jozoé Baccin (2019)
This article aims to analyze the teacher's role in the prevention and resolution of conflicts, aiming to combat violence and disseminate a Culture of Peace in the school environment. The methodology used in the article was a literature review, being used mainly the authors Durkheim, Paulo Freire, Kay Pranis, Maria Tereza Maldonado Libano and Marshal Rosenberg. The article is composed of three subtitles which deal with the conceptualization of education and the importance of teacher preparation, regarding problems generated by social diversity that have impacts on the school and, finally, on the culture of peace. From the readings carried out, it was possible to conclude that the Educators are prepared to resolve conflicts generated by social diversity that are within the school environment and, through dialogue, respect and rescuing values, sowing a Culture of Peace within each of the students.